ZIF-derived high-nano-silicon-loaded silicon-carbon negative electrode material, preparation method and battery

By using nano-silicon surface modification and mechanical ball milling method in silicon-carbon anode materials, a carbon network with excellent conductivity is formed by optimizing the carbonization process, the problems of poor high load uniformity of silicon and insufficient interface bonding stability are solved, and the electrochemical performance and cyclic stability of the material are significantly improved, which is suitable for industrial batch preparation.

CN119674011APending Publication Date: 2025-03-21TIANFU JIANGXI LAB

Patent Information

Application Number
CN202411871375.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the prior art, when preparing silicon-carbon anode materials based on ZIFs, there are problems such as poor silicon load uniformity, insufficient interface bond stability, complex process and difficult to batch preparation.

Method used

Through nanosilicon surface modification, optimized structural design of ZIF materials and the introduction of silicon precursors, the high uniform distribution of nanosilicon in the carbon-based framework is achieved based on the mechanical ball milling method, and a carbon network with excellent conductivity is formed by controlling the carbonization process.

Benefits of technology

It significantly improves the electrochemical performance and cycle stability of composite materials. The silicon content can reach more than 50%, the specific capacity can exceed 1500mAh/g, and the process is simple, making it suitable for industrial batch preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674011A_ABST
    Figure CN119674011A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium batteries, and discloses a ZIF-derived high-nano-silicon-loaded silicon-carbon negative electrode material, a preparation method and a battery, and the preparation method comprises the following steps: S1, surface modification of nano silicon; s2, preparing a ZIF precursor solution; s3, mixing the surface modified nano silicon with the ZIF precursor solution, and compounding by adopting mechanical ball milling; and S4, carrying out carbonization treatment on the composite material to prepare the ZIF-derived high-nano-silicon-loaded silicon-carbon negative electrode material. According to the preparation method disclosed by the invention, high-uniformity distribution of nano silicon in a carbon-based skeleton is realized based on a mechanical ball-milling method by modifying the surface of the nano silicon, optimizing the structural design of a ZIF material and introducing a silicon precursor, and a carbon network with excellent conductivity is formed by controlling a carbonization process, so that the electrochemical performance and the cycling stability of the composite material are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a ZIF-derived high-load nano-silicon silicon-carbon negative electrode material and a preparation method and a battery. Background Art

[0002] Silicon-carbon negative electrode materials have become a research hotspot for the new generation of high-energy-density lithium batteries due to their high theoretical specific capacity (3579mAh / g) and low discharge potential in lithium-ion batteries. However, since the volume change of silicon during charging and discharging is as high as 300% or more, it is easy to cause electrode structure rupture and poor electrode-electrolyte interface stability, which seriously affects its cycle life and rate performance. Therefore, silicon-based negative electrode materials need to be compounded with carbon-based materials to alleviate the volume effect of silicon and improve conductivity.

[0003] In recent years, researchers have developed a variety of silicon-carbon composite material preparation technologies, such as sol-gel method, chemical vapor deposition (CVD), high-temperature pyrolysis method and mechanical mixing method. Although these methods can improve the performance of silicon-carbon negative electrodes, they still have the following problems in practical applications: (1) Uneven distribution of silicon: In traditional preparation processes, silicon particles are often unevenly distributed in the carbon-based skeleton, resulting in local stress concentration and poor cycle stability; (2) Insufficient interface stability: The combination of silicon and carbon is mostly physical mixing, the interface bonding strength is low, and interface stratification or peeling is prone to occur during the charge and discharge cycle; (3) Complex process and high cost: Many methods involve complex multi-step reactions and expensive precursor raw materials, which are difficult to achieve industrial large-scale production.

[0004] Metal-organic frameworks (MOFs) have become a new template material for the preparation of silicon-carbon composites due to their highly controllable pore structure, adjustable chemical composition and excellent thermal stability. Among them, zeolite imidazole frameworks (ZIFs) are widely used in the construction of multifunctional composites due to their high specific surface area, easy morphology control and excellent conductivity after carbonization. However, the current research on the preparation of silicon-carbon negative electrode materials based on ZIFs is still concentrated in the laboratory stage, and the batch preparation method is not yet mature. There are the following problems: (1) High silicon loading is difficult to achieve: In the existing technology, ZIFs as templates are usually difficult to load high content of nano-silicon, resulting in limited actual capacity contribution of silicon in the prepared composite materials; (2) Imperfect conductive network construction: During the preparation process, the carbon in the carbonization product is unevenly distributed and the conductivity is poor, which cannot give full play to the high specific capacity characteristics of silicon; (3) The process is complicated and difficult to prepare in batches: The existing ZIF synthesis still mainly adopts the solvent method, and the preparation of its derivative materials usually requires complex conditions such as high temperature and inert atmosphere, so batch preparation is still challenging.

[0005] In summary, the existing technology still has obvious deficiencies in the uniformity of silicon high loading, interface bonding stability and process industrial feasibility of silicon-carbon composite materials.

[0006] In view of this, this application is hereby filed. Summary of the invention

[0007] The problem with the prior art is that the ZIFs-based silicon-carbon negative electrode materials prepared by the traditional sol-gel method and other technologies are still insufficient in terms of high silicon loading uniformity, interface bonding stability and process industrial feasibility. A ZIF-derived high-load nano-silicon silicon-carbon negative electrode material and a preparation method and a battery are provided. By modifying the surface of nano-silicon, optimizing the structural design of the ZIF material and the introduction of the silicon precursor, a highly uniform distribution of nano-silicon in the carbon-based skeleton is achieved based on the mechanical ball milling method, and a carbon network with excellent conductivity is formed by controlling the carbonization process, thereby significantly improving the electrochemical performance and cycle stability of the composite material.

[0008] The present invention is achieved through the following technical solutions:

[0009] In a first aspect, the present invention provides a ZIF-derived silicon-carbon negative electrode material with high nano-silicon loading, comprising the following steps:

[0010] S1, surface modified nanosilicon;

[0011] S2, preparing ZIF precursor solution;

[0012] S3, mixing the surface modified nano-silicon with the ZIF precursor solution and compounding by mechanical ball milling;

[0013] S4, carbonizing the composite material to obtain a ZIF-derived silicon-carbon negative electrode material with high nano-silicon loading.

[0014] The present invention achieves highly uniform distribution of nano-silicon in the carbon-based skeleton through surface modification of nano-silicon, optimization of the structural design of ZIF materials and the introduction method of silicon precursors based on mechanical ball milling, and forms a carbon network with excellent conductivity by controlling the carbonization process, thereby significantly improving the electrochemical performance and cycle stability of the composite material.

[0015] In a specific implementation, the specific method of step S1 is as follows:

[0016] Dispersing nano-silicon in dilute nitric acid or hydrogen peroxide solution, stirring at room temperature to 60° C. for 1 to 3 hours to form a silicon oxide film, thereby obtaining nano-silicon modified with silicon oxide surface;

[0017] Dispersing the oxidized modified nano-silicon into an ethanol or methanol solution, adding a modifying agent, and stirring at 60 to 80° C. for 6 to 12 hours to perform surface modification to obtain surface-modified nano-silicon;

[0018] The surface-modified nano-silicon is subjected to airflow classification and screening to obtain uniform particles with a particle size distribution in the range of 20 to 50 nm.

[0019] The present invention improves the dispersibility and activity of nano-silicon through surface oxidation and organic functional modification, and improves the binding ability of nano-silicon and ZIF precursor, thereby improving the high load and uniformity of the composite material.

[0020] In a specific embodiment, the concentration of the dilute nitric acid or hydrogen peroxide solution is 3% to 10%.

[0021] In a specific embodiment, the modifier is a functional modifier, using an imidazole compound, and the molar ratio of the nano-silicon modified on the surface of silicon oxide to the imidazole compound is 1:3 to 1:5;

[0022] Alternatively, the modifier is a surface modifier, which is polyvinyl pyrrolidone (PVP), cetyltrimethylammonium bromide (CTAB) or sodium polystyrene sulfonate (PSS), and the mass ratio of the nano-silicon modified on the silicon oxide surface to the surface modifier is 1:2 to 1:10.

[0023] In a specific embodiment, in step S2, the ZIF precursor solution includes Zn salt and organic ligand, and the mass ratio of surface-modified nano-silicon, Zn salt and organic ligand is 1:1:2 to 1:1:10.

[0024] In a specific implementation, the specific method of step S3 is as follows:

[0025] Dispersing the surface-modified nanosilicon in anhydrous methanol and stirring;

[0026] Add Zn salt, stir and then add 2-methylimidazole, continue stirring, transfer to a ball mill, the ball mill speed is 200-500rpm, the ball-to-material ratio is 10:1-15:1, the ball mill time is 2-12h, after the reaction is completed, dry to obtain a composite material powder.

[0027] Specifically, the Zn salt is Zn(NO3)2, and the organic ligand is 2-methylimidazole.

[0028] The present invention realizes the compounding of nano-silicon and ZIF precursor by mechanical ball milling. During this process, silicon particles can be evenly coated in the primary network formed by the ZIF precursor, achieving high uniform loading of nano-silicon, so that the silicon content can reach more than 50%, significantly improving the specific capacity of the silicon-carbon negative electrode material.

[0029] In a specific implementation, the specific method of step S4 is as follows:

[0030] The composite material powder is placed in a carbonization furnace, introduced into a reducing atmosphere, and sintered;

[0031] The sintering temperature is first raised to 400-500°C at a rate of 2-10°C / min, maintained for 1-2 hours, and then raised to 800-1000°C, maintained for 2-4 hours.

[0032] The present invention converts the nano-silicon @ ZIF composite material into a silicon-carbon composite structure with high conductivity through a controllable pyrolysis process. During the pyrolysis process, the atmosphere and temperature control optimize the interaction between silicon particles and carbon-based structures, prevent silicon particles from agglomerating, optimize the conductive network and silicon-carbon interface, form a stable silicon-carbon interface and a continuous conductive network, ensure the connectivity and conductivity of the carbon network, not only provide an excellent electron conduction path, but also effectively alleviate the volume effect of silicon, while significantly improving the material's cycle stability and rate performance.

[0033] In addition, conventional reducing atmosphere control equipment is used in the pyrolysis process, avoiding the need for special conditions (such as ultra-high temperature or high pressure) and having good industrial operability.

[0034] In a second aspect, the present invention provides a ZIF-derived silicon-carbon negative electrode material with high nano-silicon loading, which is prepared by the preparation method.

[0035] In a third aspect, the present invention provides the use of the ZIF-derived silicon-carbon negative electrode material with high nano-silicon loading, or the ZIF-derived silicon-carbon negative electrode material with high nano-silicon loading obtained by the preparation method in a lithium-ion battery.

[0036] In a fourth aspect, a lithium-ion battery comprises a positive electrode and a negative electrode, wherein the negative electrode adopts the ZIF-derived silicon-carbon negative electrode material with high nano-silicon loading, or the ZIF-derived silicon-carbon negative electrode material with high nano-silicon loading obtained by the preparation method.

[0037] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0038] 1. A ZIF-derived silicon-carbon negative electrode material with high nano-silicon loading, a preparation method, and a battery provided in an embodiment of the present invention achieves highly uniform distribution of nano-silicon in a carbon-based skeleton by surface modification of nano-silicon, optimization of the structural design of the ZIF material, and introduction of a silicon precursor based on a mechanical ball milling method, and forms a carbon network with excellent conductivity by controlling the carbonization process, thereby enhancing the bonding force between silicon and the carbon-based skeleton, avoiding interface stratification and performance attenuation, and thus significantly improving the electrochemical performance and cycle stability of the composite material;

[0039] 2. A ZIF-derived silicon-carbon negative electrode material with high nano-silicon loading, a preparation method, and a battery provided in an embodiment of the present invention improves the dispersibility and activity of nano-silicon through surface oxidation and organic functionalization modification, and improves the binding ability of nano-silicon with ZIF precursor, thereby improving the high loading and uniformity of the composite material;

[0040] 3. A ZIF-derived silicon-carbon negative electrode material with high nano-silicon loading, a preparation method, and a battery provided in an embodiment of the present invention realizes the composite of nano-silicon and ZIF precursor by mechanical ball milling. During this process, silicon particles can be evenly coated in the primary network formed by the ZIF precursor, realizing high uniform loading of nano-silicon, so that the silicon content can reach more than 50%, significantly improving the specific capacity of the silicon-carbon negative electrode material, which can exceed 1500mAh / g;

[0041] 4. A ZIF-derived silicon-carbon negative electrode material with high nano-silicon loading, a preparation method, and a battery provided in an embodiment of the present invention optimizes the interaction between silicon particles and carbon-based structures by controlling the atmosphere and temperature during the pyrolysis process, prevents silicon particles from agglomerating, optimizes the conductive network and the silicon-carbon interface, forms a stable silicon-carbon interface and a continuous conductive network, ensures the connectivity and conductivity of the carbon network, not only provides an excellent electron conduction path, but also effectively alleviates the volume effect of silicon, and significantly improves the cycle stability and rate performance of the material;

[0042] 5. A ZIF-derived silicon-carbon negative electrode material with high nano-silicon loading, a preparation method, and a battery provided in an embodiment of the present invention have a simple process flow, and can achieve kilogram-level mass production of materials through continuous ball mechanical milling and reducing atmosphere pyrolysis technology, thereby simplifying the traditional complex multi-step synthesis process, reducing production costs and time costs, and improving preparation efficiency;

[0043] 6. A ZIF-derived high-load nano-silicon silicon-carbon negative electrode material, a preparation method, and a battery provided in an embodiment of the present invention can maintain a capacity retention rate of more than 80% in a long cycle (more than 300 times), showing excellent electrochemical stability. At the same time, at a current density of 1A / g, the material can exhibit a specific capacity of more than 1200mAh / g, and the rate performance is significantly better than that of traditional silicon-carbon negative electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0045] Figure 1A schematic diagram of the preparation process of the p-Si NPs@CN composite silicon-based negative electrode material provided in an embodiment of the present invention;

[0046] Figure 2 Schematic diagram of the microstructure of the p-Si NPs@CN composite silicon-based negative electrode material provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0047] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments and drawings. The exemplary embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0048] In the following description, a large number of specific details are set forth in order to provide a thorough understanding of the present invention. However, it is apparent to one of ordinary skill in the art that these specific details need not be employed to practice the present invention. In other embodiments, in order to avoid obscuring the present invention, well-known materials or methods are not specifically described.

[0049] Throughout the specification, references to "one embodiment," "an embodiment," "an example," or "an example" mean that a particular feature, structure, or characteristic described in conjunction with the embodiment or example is included in at least one embodiment of the present invention. Therefore, the phrases "one embodiment," "an embodiment," "an example," or "an example" appearing in various places throughout the specification do not necessarily all refer to the same embodiment or example. In addition, particular features, structures, or characteristics may be combined in one or more embodiments or examples in any suitable combination and / or subcombination. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0050] Research on the preparation of silicon-carbon negative electrode materials based on ZIFs is still concentrated in the laboratory stage, and the batch preparation method is not yet mature. There are the following problems: (1) High silicon loading is difficult to achieve: In the existing technology, ZIFs as templates are usually difficult to load high content of nano-silicon, resulting in limited actual capacity contribution of silicon in the prepared composite materials; (2) Imperfect conductive network construction: During the preparation process, the carbon in the carbonization product is unevenly distributed and has poor conductivity, which cannot fully exert the high specific capacity characteristics of silicon; (3) The process is complex and difficult to prepare in batches: The existing ZIF synthesis still mainly adopts the solvent method, and the preparation of its derivative materials usually requires complex conditions such as high temperature and inert atmosphere, and batch preparation still faces challenges.

[0051] In order to solve the above technical problems,

[0052] like Figure 1 As shown, in the first aspect, the present invention provides a ZIF-derived silicon-carbon negative electrode material with high nano-silicon loading, comprising the following steps:

[0053] S1, surface modified nanosilicon;

[0054] 1) Oxidation treatment

[0055] Disperse nano-silicon in dilute nitric acid or hydrogen peroxide solution (concentration is 3% to 10%), stir at room temperature to 60° C. for 1 to 3 hours to form a silicon oxide film.

[0056] The product was fully washed with deionized water until neutral, and dried at 120° C. to obtain nano-silicon modified with silicon oxide surface.

[0057] 2) Organic functional modification:

[0058] The oxidized nano-silicon is dispersed in an ethanol or methanol solution, and an imidazole compound (such as 2-methylimidazole, with a molar ratio of nano-silicon:imidazole = 1:3 to 1:5) is added, and stirred at 60 to 80° C. for 6 to 12 hours.

[0059] The unreacted imidazole compounds were removed by filtration and washed, and the mixture was dried at 120° C. to obtain surface functionalized nano-silicon.

[0060] 3) Surface modification:

[0061] The oxidized nano-silicon is dispersed in an ethanol or methanol solution, and a surface modifier (such as polyvinyl pyrrolidone (PVP), hexadecyltrimethylammonium bromide (CTAB) or sodium polystyrene sulfonate (PSS) with a mass ratio of nano-silicon: surface modifier = 1:2 to 1:10) is added, and stirred at 60 to 80°C for 6 to 12 hours.

[0062] 4) Particle size control:

[0063] The surface-modified nano-silicon is subjected to airflow classification and screening to obtain uniform particles with a particle size distribution in the range of 20 to 50 nm; and ultrasonic dispersion technology is used to further optimize the particle dispersibility.

[0064] S2, preparing ZIF precursor solution;

[0065] A ZIF precursor solution (including metal salt, such as Zn(NO3)2, and organic ligand 2-methylimidazole) is prepared in a mass ratio of surface-modified nano-silicon: Zn salt: organic ligand = 1:1:2 to 1:1:10.

[0066] S3, mixing the surface modified nano-silicon with the ZIF precursor solution and compounding by mechanical ball milling;

[0067] Dispersing the surface-modified nanosilicon in anhydrous methanol and stirring;

[0068] Add Zn salt, stir and then add 2-methylimidazole. After continuous stirring, transfer to a ball mill with a ball mill speed of 200 to 500 rpm, a ball-to-material ratio of 10:1 to 15:1, and a ball mill time of 2 to 12 hours. After the reaction is completed, dry to obtain a composite material powder. During this process, the silicon particles are evenly coated in the primary network formed by the ZIF precursor.

[0069] S4, carbonizing the composite material to obtain a ZIF-derived silicon-carbon negative electrode material with high nano-silicon loading.

[0070] Use a tubular furnace or a box furnace, and introduce a 0%-20% hydrogen / nitrogen mixture as a protective atmosphere, with the flow rate controlled at 100-300 mL / min; initial heating stage: from room temperature to 400-500°C at a rate of 2-10°C / min, maintain for 1-2 hours to remove organic ligands; high-temperature carbonization stage: further heat to 800-1000°C, maintain for 2-4 hours to generate a highly conductive carbon network and stabilize the silicon-carbon interface; cooling stage: naturally cool to room temperature.

[0071] The method for preparing a ZIF-derived silicon-carbon negative electrode material with high nano-silicon loading in the present invention specifically comprises the following steps: Figure 1 The steps shown are as follows: (1) surface modification of nano-silicon, mainly surface oxidation of nano-silicon and uniform modification of the surface of nano-silicon with organic compounds, providing conditions for uniform encapsulation of nano-silicon by ZIF; (2) high-load uniform encapsulation of Si NPs by ZIF-8, this step mainly realizes the in-situ growth of ZIF-8 on the surface of modified nano-silicon, realizes high-load uniform encapsulation of nano-silicon by ZIF-8, and mechanical ball milling can achieve kilogram-level macro-scale preparation; (3) controllable carbonization of silicon@ZIF-8 composite materials, this step mainly realizes the transformation of ZIF-8 into a high-porosity, high-conductivity carbon matrix; (4) finally, the performance of the silicon-carbon negative electrode material is evaluated, this step mainly realizes the lithium battery performance evaluation of the material, and tests its energy density, cycle life, etc.

[0072] The present invention achieves highly uniform distribution of nano-silicon in the carbon-based skeleton through surface modification of nano-silicon, optimization of the structural design of ZIF materials and the introduction method of silicon precursors based on mechanical ball milling, and forms a carbon network with excellent conductivity by controlling the carbonization process, thereby significantly improving the electrochemical performance and cycle stability of the composite material.

[0073] The present invention realizes the compounding of nano-silicon and ZIF precursor by mechanical ball milling. During this process, silicon particles can be evenly coated in the primary network formed by the ZIF precursor, achieving high uniform loading of nano-silicon, so that the silicon content can reach more than 50%, significantly improving the specific capacity of the silicon-carbon negative electrode material.

[0074] The present invention converts the nano-silicon @ ZIF composite material into a silicon-carbon composite structure with high conductivity through a controllable pyrolysis process. During the pyrolysis process, the atmosphere and temperature control optimize the interaction between silicon particles and carbon-based structures, prevent silicon particles from agglomerating, optimize the conductive network and silicon-carbon interface, form a stable silicon-carbon interface and a continuous conductive network, ensure the connectivity and conductivity of the carbon network, not only provide an excellent electron conduction path, but also effectively alleviate the volume effect of silicon, while significantly improving the material's cycle stability and rate performance.

[0075] In addition, conventional reducing atmosphere control equipment is used in the pyrolysis process, avoiding the need for special conditions (such as ultra-high temperature or high pressure) and having good industrial operability.

[0076] In a second aspect, the present invention provides a ZIF-derived silicon-carbon negative electrode material with high nano-silicon loading, which is prepared by the preparation method.

[0077] In a third aspect, the present invention provides the use of the ZIF-derived silicon-carbon negative electrode material with high nano-silicon loading, or the ZIF-derived silicon-carbon negative electrode material with high nano-silicon loading obtained by the preparation method in a lithium-ion battery.

[0078] In a fourth aspect, the present invention provides a lithium-ion battery comprising a positive electrode and a negative electrode, wherein the negative electrode adopts the ZIF-derived silicon-carbon negative electrode material with high nano-silicon loading, or the ZIF-derived silicon-carbon negative electrode material with high nano-silicon loading obtained by the preparation method.

[0079] Example 1

[0080] The embodiment of the present invention provides a method for preparing a ZIF-derived silicon-carbon negative electrode material with high nano-silicon loading, comprising the following steps:

[0081] Step 1: Surface modification of nano-silicon (p-Si NPs)

[0082] 1) First, the nano-silicon particles are oxidized:

[0083] 2 kg of nano-silicon was dispersed in a hydrogen peroxide solution (concentration of 10%), and stirred for 2 hours at room temperature to 60°C to form a silicon oxide film, which was fully washed with deionized water and vacuum dried at 80°C to obtain nano-silicon with silicon oxide surface modified.

[0084] 2) Then carry out organic functional modification on its surface:

[0085] The surface-oxidized nano-silicon was dispersed in an ethanol solution, and a surface modifier (sodium polystyrene sulfonate (PSS), with a mass ratio of nano-silicon: surface modifier = 1:2 to 1:10) was added, and stirred at 60°C for 8 hours. After filtering, washing, and drying, the nano-silicon was subjected to airflow classification and screening to obtain uniform particles with a particle size distribution in the range of 20 to 50 nm.

[0086] Step 2: In situ growth of ZIF-8 on nano-Si surfaces (p-Si NPs@ZIF-8)

[0087] Disperse 2kg of the surface-modified nano-silicon (p-Si NPs) in 15L of methanol solution and stir for 30min. Add 3kg of zinc nitrate to the reaction solution and stir for 15min, then add 3kg of 2-methylimidazole. Continue stirring for 30min, transfer to a ball mill, control the ball mill speed to 400rpm, the ball-to-material ratio to 10:1, and the ball milling time to 4h. After the reaction is completed, dry in a vacuum oven at 60℃ for 4h to obtain a composite material powder.

[0088] Step 3: Carbonization treatment of p-Si NPs@ZIF-8

[0089] The above 4kg composite material powder (p-Si NPs@ZIF-8) was placed in a carbonization furnace, and a 10% hydrogen / nitrogen reducing atmosphere was introduced for sintering to obtain a finished material. The reducing atmosphere was introduced for 0.5h before carbonization, and the carbonization furnace was heated to 800°C at a rate of 5°C / min. The sintering time was 4h. The prepared product was recorded as p-Si NPs@CN (Si content was about 56.9wt.%).

[0090] The p-Si NPs@CN negative electrode material was mixed with PVDF and Super P in a mass ratio of 8:1:1 to form a slurry, which was coated on the copper foil current collector and finally made into a CR2032 button battery for testing. The test voltage window was 0-3V.

[0091] Comparative Example 1

[0092] This comparative example provides a method for preparing a silicon-carbon negative electrode material, comprising the following steps:

[0093] Step 1: Surface modification of nano-silicon (p-Si NPs)

[0094] 1) First, the nano-silicon particles are oxidized:

[0095] 2 kg of nano-silicon was dispersed in a hydrogen peroxide solution (concentration of 10%), and stirred for 2 hours at room temperature to 60°C to form a silicon oxide film, which was fully washed with deionized water and vacuum dried at 80°C to obtain nano-silicon with silicon oxide surface modified.

[0096] 2) Then carry out organic functional modification on its surface:

[0097] The surface-oxidized nano-silicon was dispersed in an ethanol solution, and a surface modifier (sodium polystyrene sulfonate (PSS), with a mass ratio of nano-silicon: surface modifier = 1:2 to 1:10) was added, and stirred at 60°C for 8 hours. After filtering, washing, and drying, the nano-silicon was subjected to airflow classification and screening to obtain uniform particles with a particle size distribution in the range of 20 to 50 nm.

[0098] Step 2: Preparation of p-Si NPs@ZIF-8 by spray drying

[0099] The surface-modified nano-silicon particles were mixed with the ZIF-8 precursor solution at a mass ratio of 1:3 and subjected to ultrasonic dispersion treatment for 60 minutes;

[0100] Using a spray dryer, the mixed solution was sprayed into a drying tower at a temperature of 100°C at a rate of 15 mL / min to obtain precursor particles, namely p-Si NPs@ZIF-8.

[0101] Step 3: Carbonization treatment of p-Si NPs@ZIF-8

[0102] The above 4 kg material powder (p-Si NPs@ZIF-8) was placed in a carbonization furnace, and a 10% hydrogen / nitrogen reducing atmosphere was introduced for sintering to obtain the finished material. The reducing atmosphere was introduced for 0.5 h before carbonization, and the carbonization furnace was heated to 800 ° C at a rate of 5 ° C / min, and the sintering time was 4 h.

[0103] The prepared silicon-carbon negative electrode material was mixed with PVDF and Super P in a mass ratio of 8:1:1 to form a slurry, which was coated on a copper foil current collector and finally made into a CR2032 button battery for testing, with a test voltage window of 0-3V.

[0104] Comparative Example 2

[0105] This comparative example provides a method for preparing a silicon-carbon negative electrode material, comprising the following steps:

[0106] Step 1: Surface modification of nano-silicon (p-Si NPs)

[0107] 1) First, the nano-silicon particles are oxidized:

[0108] 2 kg of nano-silicon was dispersed in a hydrogen peroxide solution (concentration of 10%), and stirred for 2 hours at room temperature to 60°C to form a silicon oxide film, which was fully washed with deionized water and vacuum dried at 80°C to obtain nano-silicon with silicon oxide surface modified.

[0109] 2) Then carry out organic functional modification on its surface:

[0110] The surface-oxidized nano-silicon was dispersed in an ethanol solution, and a surface modifier (sodium polystyrene sulfonate (PSS), with a mass ratio of nano-silicon: surface modifier = 1:2 to 1:10) was added, and stirred at 60°C for 8 hours. After filtering, washing, and drying, the nano-silicon was subjected to airflow classification and screening to obtain uniform particles with a particle size distribution in the range of 20 to 50 nm.

[0111] Step 2: Preparation of p-Si NPs@ZIF-8 by supercritical fluid deposition

[0112] First, the surface-modified nano-silicon particles were dispersed in the ZIF precursor solution, and supercritical CO2 solvent was added to control the mass ratio of silicon to precursor to 1:3. The solution was maintained in an autoclave at a pressure of 15 MPa and a temperature of 60°C for 4 hours to allow the ZIF precursor to be uniformly deposited on the surface of the silicon particles. After filtration, washing, and drying, p-Si NPs@ZIF-8 was obtained.

[0113] Step 3: Carbonization treatment of p-Si NPs@ZIF-8

[0114] The above 4 kg material powder (p-Si NPs@ZIF-8) was placed in a carbonization furnace, and a 10% hydrogen / nitrogen reducing atmosphere was introduced for sintering to obtain the finished material. The reducing atmosphere was introduced for 0.5 h before carbonization, and the carbonization furnace was heated to 800 ° C at a rate of 5 ° C / min, and the sintering time was 4 h.

[0115] The prepared silicon-carbon negative electrode material was mixed with PVDF and Super P in a mass ratio of 8:1:1 to form a slurry, which was coated on a copper foil current collector and finally made into a CR2032 button battery for testing, with a test voltage window of 0-3V.

[0116] Comparative Example 3

[0117] This comparative example provides a method for preparing a silicon-carbon negative electrode material. Compared with Example 1, no nano-silicon particles are added in step 2, ZIF-8 particles are directly synthesized, and the heat treatment in step 3 is performed to obtain a CN material.

[0118] The CN material, PVDF and Super P were mixed and stirred in a mass ratio of 8:1:1 to form a slurry, which was coated on a copper foil current collector and finally made into a CR2032 button battery for testing. The test voltage window was 0-3V.

[0119] Comparative Example 4

[0120] This comparative example provides a method for preparing a silicon-carbon negative electrode material. Compared with Example 1, it only includes step 1 of preparing nano-silicon (p-Si NPs) modified with silicon oxide surface.

[0121] Si NPs, PVDF and Super P were mixed and stirred in a mass ratio of 8:1:1 to form a slurry, which was coated on a copper foil current collector and finally made into a CR2032 button battery for testing with a test voltage window of 0-3V.

[0122] The negative electrode materials and batteries prepared in Example 1 and Comparative Examples 1-4 were subjected to corresponding performance tests, such as Figure 2 As shown in Table 1. Figure 2 The schematic diagram of the microstructure of the p-Si NPs@CN composite silicon-based negative electrode material prepared in Example 1. It can be seen that the nano-sized silicon particles are evenly distributed in the ZIF-derived carbon shell, the nano-silicon is embedded in the carbon matrix, and an obvious porous structure is formed, which can fully accommodate the volume expansion of the nano-silicon during the cycle, reduce the charge and discharge expansion effect of the composite negative electrode material, and improve the cycle stability; and the highly crystalline carbon is evenly coated around the nano-silicon to form a core-shell structure, which provides a fast and highly conductive path and greatly improves the conductive properties of the material.

[0123] Table 1 is the electrochemical performance test results of the batteries obtained in Example 1 and Comparative Examples 1-4. It can be found that Example 1 has the best comprehensive performance, while Comparative Example 1 (spray drying method) and Comparative Example 2 (supercritical fluid deposition method) also have higher reversible specific capacity and cycle life, but the preparation process is more complicated and the preparation cost is higher. In addition, in the process of ZIF-8 coating nano-silicon by spray drying method, ZIF-8 cannot form micron-sized Si@ZIF-8 aggregates, so it is impossible to form a high-porosity carbon matrix with a sponge structure, so its cycle stability is not high. In Comparative Example 2, the Si@ZIF-8 particles formed have a smaller particle size, so the pores produced are less, and the silicon loading is lower than that of the mechanical ball milling method, so its first reversible specific capacity and cycle retention rate are finally low. Comparative Example 3 (CN material derived from ZIF-8) has a lower specific capacity due to the lack of lithium storage active material silicon. Although the single silicon nanoparticles in Comparative Example 4 have a high first reversible specific capacity, the cycle stability is poor.

[0124] Table 1

[0125]

[0126] Table 2 shows a comprehensive comparison of the batch preparation processes of various silicon-carbon negative electrode materials. The mechanical ball milling method used in the present invention has the characteristics of low equipment cost, simple process procedure, moderate product uniformity, and high performance of the final product. It is suitable for kilogram-level batch preparation and is the most cost-effective batch preparation method compared to spray drying-pyrolysis, supercritical fluid deposition, fluidized bed CVD, and solid-state melt coating. For the present invention, the mechanical ball milling process is used to realize ZIF-8 encapsulation of modified nano-silicon compared to the solvent thermal method, and the raw material loss rate is reduced by about 60%, the solvent consumption is reduced by 90%, and the process time in step (2) is reduced from about 30 hours of the solvent thermal method to about 8 hours. Therefore, the preparation process of the present invention has the advantages of short time consumption, less solvent usage, and low raw material waste rate.

[0127] Table 2

[0128]

[0129] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A ZIF-derived silicon-carbon negative electrode material with high nano-silicon loading, characterized in that: The steps include: S1, surface modified nanosilicon; S2, preparing ZIF precursor solution; S3, mixing the surface modified nano-silicon with the ZIF precursor solution and compounding by mechanical ball milling; S4, carbonizing the composite material to obtain a ZIF-derived silicon-carbon negative electrode material with high nano-silicon loading.

2. The ZIF-derived silicon-carbon negative electrode material with high nano-silicon loading according to claim 1, characterized in that: The specific method of step S1 is as follows: Dispersing nano-silicon in dilute nitric acid or hydrogen peroxide solution for oxidation treatment to form a silicon oxide film to obtain nano-silicon with silicon oxide surface modified; The oxidized modified nano-silicon is dispersed in an ethanol or methanol solution, and a modifier is added for surface modification to obtain surface modified nano-silicon.

3. The ZIF-derived silicon-carbon negative electrode material with high nano-silicon loading according to claim 2, characterized in that: The concentration of dilute nitric acid or hydrogen peroxide solution is 3% to 10%.

4. The method for preparing a ZIF-derived silicon-carbon negative electrode material with high nano-silicon loading according to claim 2, characterized in that: The modifier is a functional modifier, using an imidazole compound, and the molar ratio of the nano-silicon modified on the surface of silicon oxide to the imidazole compound is 1:3 to 1:5; Alternatively, the modifier is a surface modifier, which is polyvinyl pyrrolidone (PVP), cetyltrimethylammonium bromide (CTAB) or sodium polystyrene sulfonate (PSS), and the mass ratio of the nano-silicon modified on the silicon oxide surface to the surface modifier is 1:2 to 1:

10.

5. The method for preparing a ZIF-derived silicon-carbon negative electrode material with high nano-silicon loading according to claim 1, characterized in that: In step S2, the ZIF precursor solution includes Zn salt and organic ligand, and the mass ratio of surface modified nano-silicon, Zn salt and organic ligand is 1:1:2 to 1:1:

10.

6. The method for preparing a ZIF-derived silicon-carbon negative electrode material with high nano-silicon loading according to claim 1, characterized in that: The specific method of step S3 is as follows: Dispersing the surface modified nano-silicon in a methanol solution and stirring; Add Zn salt, stir and then add 2-methylimidazole, continue stirring, transfer to a ball mill, the ball mill speed is 200-500rpm, the ball-to-material ratio is 10:1-15:1, the ball mill time is 2-12h, after the reaction is completed, dry to obtain a composite material powder.

7. The method for preparing a ZIF-derived silicon-carbon negative electrode material with high nano-silicon loading according to claim 1, characterized in that: The specific method of step S4 is as follows: The composite material powder is placed in a carbonization furnace, introduced into a reducing atmosphere, and sintered; The sintering temperature is first raised to 400-500°C at a rate of 2-10°C / min, maintained for 1-2 hours, and then raised to 800-1000°C, maintained for 2-4 hours.

8. A ZIF-derived silicon-carbon negative electrode material with high nano-silicon loading, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the ZIF-derived silicon-carbon negative electrode material with high nano-silicon loading as claimed in claim 8, or the ZIF-derived silicon-carbon negative electrode material with high nano-silicon loading obtained by the preparation method of any one of claims 1 to 7 in lithium-ion batteries.

10. A lithium ion battery comprising a positive electrode and a negative electrode, characterized in that: The negative electrode adopts the ZIF-derived silicon-carbon negative electrode material with high nano-silicon loading as described in claim 9, or the ZIF-derived silicon-carbon negative electrode material with high nano-silicon loading obtained by any one of the preparation methods described in claims 1 to 7.

Citation Information

Patent Citations

  • Si@C lithium-ion battery negative electrode material of core-shell structure and preparation method thereof

    CN107359326A

  • Silicon-based negative electrode material and preparation method and application thereof

    CN110729472A

  • Preparation method of silicon-carbon composite anode material

    CN112467136A

  • Preparation method of silicon-carbon negative electrode material of lithium ion battery

    CN112768670A

  • Self-supporting nitrogen-doped porous carbon-coated silicon nanofiber material for negative electrode of lithium ion battery as well as preparation method and application of self-supporting nitrogen-doped porous carbon-coated silicon nanofiber material

    CN113629251A

Cited By

  • Modified pole piece for energy storage and polymer solid-state battery

    CN121076068A